CULTIVATION OF LEADERSHIP CHARACTER ON EARLY CHILDHOOD THROUGH THE STORY OF QUEEN BALQIS - Ria Astuti (Sunan Kalijaga International Journal on Islamic Educational Research, 2018)
This article aims to know how the method of planting leadership character into early childhood through the story of Queen Balqis. The story of Queen Balqis is recounted in the Qur'an surah an-Naml. The story of Queen Balqis originated from the news brought by the bird Hud-Hud to the Prophet Sulaiman about a country led by a woman. The land of Saba ' was called by God in the Qur'an as the country of Baldatun thoyyibatun wa robbun ghofurun (a safe and prosper country and receiving forgiveness from God). There are several characteristics of Queen Balqis, namely: have a big effect, democratic, intelligent, giving priority to the safety of her people and the Knights-at-heart. The period of early childhood is the period of the golden age, which at this time is very important to develop the character of children's leadership to become qualified leaders and private. The method of planting leadership character into early childhood through the story of Queen Balqis could be through the way of watching movies, talking, conversation, role-playing, and the example method of conditioning.